Knowledge About Cervical Cancer of Pharmacy Students at the University of Medicine and Pharmacy, Hanoi National University, and Some Related Factors - Thi Phuong Lan, Nguyen; Thi Tam, Ngo; Lan Anh, Ngo; Thi Quynh, Nguyen; Hieu Duong, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2024)
Objective: Describe the current state of knowledge about cervical cancer of students of the Faculty of Pharmacy at the University of Medicine and Pharmacy - Hanoi National University in 2023 and some related factors. Subject and method: Cross-sectional study conducted via an online survey on 234 Pharmacy students at Hanoi National University of Medicine and Pharmacy in 2023. Results: The proportion of students participating in the study with passing scores on knowledge about cervical cancer was 53.8%. 23.5% of students incorrectly answered that breast cancer was also a risk factor for cervical cancer. 90.2% of students knew that cervical cancer can be detected early through screening. Very few students correctly answered the frequency of cervical cancer screening and the appropriate age for screening. Regarding cervical cancer screening, most students had heard about HPV DNA testing and Pap smears; however, the VIA test method was hardly known among students. The percentage of students with knowledge about cervical cancer increased gradually over the school years. Females had significantly higher knowledge (59.1% > 35.8%). Students who had talked to their families about sex, heard of HPV, learned about HPV through medical staff, family, friends, television or radio, or received HPV vaccination advice from medical personnel and friends had higher knowledge about cervical cancer than other groups. Conclusion: Knowledge about cervical cancer among Pharmacy students at Hanoi National University of Medicine and Pharmacy was 53.8%. Students’ knowledge about cervical cancer was related to their characteristics and their access to information.